Uporaba informacijskih virov v zdravstveni in babiški negi v Sloveniji - Dornik, Ema (Informatica Medica Slovenica, 2012)
Nurses and midwives are the largest professional group in the health care system. They have been promoting the development and acknowledgement of their field as an independent research discipline for decades. The development would be faster if they better supported their clinical work with research. Research is closely connected with knowledge and use of information resources and bibliographic databases. That topic has not been researched yet in Slovenia. The article presents a part of the results of a study on information support for nursing research and practice in our country.
Keywords: babice; babiška nega; medicinske sestre; uporaba informacijskih virov; zdravstvena nega